2014
DOI: 10.1109/tpwrd.2013.2284261
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Large-Scale Tests of Practical Grounding Electrodes—Part I: Test Facility and Measurement of Site Parameters

Abstract: This paper describes the establishment of a large-area outdoor experimental facility at the Dinorwig pumped-storage power station in North Wales for investigating the performance of practical grounding systems. The facility itself and arrangements of test electrodes and measurement equipment are described, providing a background for subsequent test methodologies. In addition, tests to determine the variation in the water and reservoir bed resistivities have been undertaken, resulting in a survey data set that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Note that A i for i=5 is time dependent. Generally, the low-frequency resistance of the electrode can be obtained from conventional measurements, although it should be noted that the measured value is sensitive to both current magnitude and its switching frequency [11,12]. The impulse index can then be determined from tests using a low-current impulse source, and used to estimate, for example, the transient ground potential rise of the electrode for any impulse current magnitude I p according to the simple expression shown in Equation (8)…”
Section: Generalized Impulse Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that A i for i=5 is time dependent. Generally, the low-frequency resistance of the electrode can be obtained from conventional measurements, although it should be noted that the measured value is sensitive to both current magnitude and its switching frequency [11,12]. The impulse index can then be determined from tests using a low-current impulse source, and used to estimate, for example, the transient ground potential rise of the electrode for any impulse current magnitude I p according to the simple expression shown in Equation (8)…”
Section: Generalized Impulse Indexmentioning
confidence: 99%
“…The nonlinear current dependence in this regime of the impulse resistance is attributed to soil ionisation and/or thermal effects. At the other end of the scale, low-magnitude current tests, which are often required for testing the grounding systems of operating installations, show that there is significant non-linear behaviour with current magnitude [11,12]. To characterise ground electrode behaviour under transient conditions, many different approaches have been adopted and several different parameters have been proposed; For example, a wide range of terms are in use e.g.…”
mentioning
confidence: 99%
“…Much work [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] has been carried out to characterize practical earthing systems under fast-impulse, high-magnitude current conditions. As generally known, experimental investigations on practical earthing systems under high impulse currents can provide more realistic results on the characteristics of earthing systems under high currents, in comparison to laboratory and computational methods.…”
Section: Introductionmentioning
confidence: 99%
“…The following year, Bellaschi [3], completed further tests on 12 earth rods, with impulse currents of 400 A to 15.5 kA. There have been a lot more impulse tests [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], were carried out on practical earthing systems, where tit was found that the 'impulse resistance' values were found to be less than those measured for low voltage, low frequency currents [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. A lot of improvements and suggestions in the impulse test methodology on practical earthing systems can also be seen in the last three decades [1][2][3][4][5][6][7][8][9][10][11][12][13][14]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation